2018
DOI: 10.2147/opth.s155611
|View full text |Cite
|
Sign up to set email alerts
|

The UK Paediatric Ocular Trauma Study 2 (POTS2): demographics and mechanisms of injuries

Abstract: PurposePediatric ocular trauma is an important cause of visual morbidity worldwide, accounting for up to one-third of all ocular trauma admissions. It has long-term implications for those affected and significant economic consequences for healthcare providers. It has been estimated that 90% of all ocular trauma is preventable. Targeted strategies are required to reduce the incidence and the severity of pediatric ocular trauma; this requires an understanding of the epidemiology and characteristics of these inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
25
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 38 publications
16
25
0
3
Order By: Relevance
“…Younger are more prone to an irresponsible behavior and lack of appreciation of potential hazards and areas of harm. This is in accordance with other published reports [9,11,12]. Being more active and more exposed to outdoor activities and sometimes even involved in childhood labor especially in developing countries and rural communities, it is not surprising that more than 70% of the injured children were males as already highlighted [2,4,9,13,14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Younger are more prone to an irresponsible behavior and lack of appreciation of potential hazards and areas of harm. This is in accordance with other published reports [9,11,12]. Being more active and more exposed to outdoor activities and sometimes even involved in childhood labor especially in developing countries and rural communities, it is not surprising that more than 70% of the injured children were males as already highlighted [2,4,9,13,14].…”
Section: Discussionsupporting
confidence: 91%
“…In an attempt to dilute this effect, the authors extended the recruitment period for one extra month and hence the 7-month study duration. The fact that pediatric ocular injuries represent almost one-third of all ocular injuries reflects how much children are a vulnerable population to ocular injuries, especially in such underprivileged communities in developing countries, which is in accordance with the findings reported by Al Wadeai et al [9], by Khan et al [10] and by Wagle et al [2] in developing countries, and is much higher than that reported by Sii et al [11] in developed countries. Within the study cohort, it is obvious that younger age groups are more vulnerable than older age groups.…”
Section: Discussionsupporting
confidence: 89%
“…A previous analysis of risk factors among 115 patients requiring surgery at Manchester Royal Eye Hospital for ocular perforation throughout 1998–2004 revealed that injury from sharp/projectile mechanisms had a 20% risk of resulting in severe visual loss or even removal of the eye 9. Of relevance, 4 cases of pencil injuries causing ocular perforation were observed in that case series (which is from our hospital) and 7 such cases in the BOSU study 8 9…”
Section: Discussionmentioning
confidence: 74%
“…The British Ophthalmological Surveillance Unit (BOSU) study found the majority of paediatric ocular trauma in the UK was sustained in environments where direct supervision of the affected children would have been expected (own home, other home, school or nursery), whereas few (14%) such injuries occurred in relatively unsupervised locations (public places or sports facilities). It follows that majority of such ocular injuries are potentially preventable through appropriate supervision by a responsible adult 8. A previous analysis of risk factors among 115 patients requiring surgery at Manchester Royal Eye Hospital for ocular perforation throughout 1998–2004 revealed that injury from sharp/projectile mechanisms had a 20% risk of resulting in severe visual loss or even removal of the eye 9.…”
Section: Discussionmentioning
confidence: 99%
“…But Puodžiuvienė et al [14] suggested that the most common type of ocular trauma was closed globe injury. Literatures showed that 90% of all ocular trauma was avoidable [23]. Figuring out the major cause of injury, it will help parents and doctors establish effective protection to reduce the incidence of ocular trauma in children.…”
Section: Discussionmentioning
confidence: 99%